Reports from China: Joan Robinson as observer and travel writer, 1953-78 - Mauro Boianovsky; Gerardo Serra (Duke University, Center for the History of Political Economy (CHOPE), 2021)
Joan Robinson's infatuation with Mao's China remains the most controversial episode of the Cambridge economist's life. Drawing on the literatures on observation in science and economics, and economists' travels, we aim at overcoming the dichotomy between Robinson as a 'political pilgrim' and as a 'development economist'. Instead, we take a closer look at her observation practices, her literary choices, and her position within different political and intellectual communities. The structure of the paper is quasi-chronological: each trip to China is described in its own right, but also treated as an entry point to shed light on a particular aspect of Robinson's engagement with the country.
Keywords: B24; B31; B50; 330; Joan Robinson; China; travel writing; observation; communities; socialism